Strategi Pembelajaran PAI Berbasis 4C (Critical Thinking, Creacifity, Collaboration, Communication) Dalam Meningkatkan Kompetensi Siswa - Melisa Kurnia Hayati; Suci Nurhidayah; Gumaneli Gumaneli (CV. ITTC INDONESIA, 2026)
This study examines the implementation of 4C-based learning strategies (Critical Thinking, Creativity, Collaboration, and Communication) in Islamic Religious Education (PAI) to enhance students’ competencies. The 4C approach emphasizes the integration of higher-order thinking skills, innovative problem-solving, teamwork, and effective communication within the learning process. This research employs a qualitative descriptive method through classroom observation, interviews, and literature review. The findings indicate that the application of 4C strategies in PAI learning encourages students to actively analyze religious concepts, express creative ideas, collaborate in group discussions, and communicate their understanding effectively. Moreover, this approach not only improves cognitive competence but also strengthens affective and social skills, such as responsibility, tolerance, and mutual respect. The integration of 4C in PAI learning creates a more interactive, meaningful, and student-centered learning environment. Therefore, 4C-based learning strategies can serve as an effective pedagogical approach to develop holistic student competencies in accordance with the demands of 21st-century education.